Brevifoliol: An Ignored cousin of Taxol - Fahad Mohammed Almutairi,; Uzma Faridi, (International Journal of Phytomedicine, 2018)
The discovery of paclitaxel, an anticancer agent was a milestone in the path of anticancer drug discovery. After approval from FDA taxol was widely used for cancer treatment. The taxol was isolated from the bark of fully grown taxus plants with is a fatal source, to overcome this problem almost all the species were investigated for the taxol and taxol like molecules. Brevifoliol is one of the many taxoid isolated from the taxus plants. The significance of brevifoliol was its source which was dried needles of plants including the Himalayan yew tree Taxus wallichiana. Brevifoliol belongs to the large group of diterpenoid cyclodecanes, the same group with which taxol belongs. In-vitro studies indicate that brevifoliol has significant activity against colon cancer cell line which is slightly better than taxol. In the present article, all the updated information and its superiority over taxol will be discussed.